A Divulgação Internacional da Arquitectura Portuguesa 1976-1988 - Cristina Emilia Ramos e Silva (2016)
Motivated by the aim of understanding the genesis of the current international acknowledgement of Portuguese contemporary architecture, the object of this dissertation is to discuss the spread and awareness of this nation's architecture beyond her own borders, focusing on the years from 1976 to 1988, its seminal period. In this dissertation we state that Portuguese architecture, often identified by metonymy with the architecture of Siza, constitutes an architectural epicenter, according to the definition by Petra Ĉeferin, with an inner quality that does not need to be validated by a hypothetical center, and therefore does not need to be self-classified as 'at the margin' or peripheral as it was described, the echoes of which can still be heard today. Given the cross-over between international theoretical-critical approaches that were being developed at that time and Portuguese architecture, international issues with relevance beyond national architecture are addressed. Additionally, ideas that had been running through the national architecture historiography will be dismantled, -ideas such as the importance of the action of the Portuguese cultural intermediaries in the international recognition of the architecture and in the building of its interpretative process, the influence of SAAL in the international commissions of Siza, and the international disclosure of Portuguese architecture as well as the emergence of the 'escola do Porto' issue. Thus, we map out the paths of the international disclosure of the Portuguese architecture, by identifying the events in which took part and the cultural intermediaries involved; we inquire into their reasoning and theoretical contexts, we identify their paths and their meetings with others cultural intermediaries. At the same time, we reveal how the international discourse as regards Portuguese architecture was filtered, passing from precanonical interpretations and centered in expressions such 'at the periphery', to canonical ones, centered in thoughts about the 'place'. Additionally, we analyze other enriching dissonant contributions. A consideration of all the events that took place during this period allowed us to prove one idea we had a priori regarding the outstanding international work and thought of Siza, showing that the disclosure of the other national architecture was made mostly in contrast with, or similarity to, the architecture of Siza.